IDENTIFICATION OF GABA-PRODUCING LACTIC ACID BACTERIA FROM CINCALOK FERMENTATION BASED ON THE 16S RRNA AND GAD GENES - PRIBADHI, ADHITYA NAUFAL; KUSDIYANTINI, ENDANG; FERNIAH, REJEKI SITI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The research to identify LAB using 16S rRNA potential as high produce GABA and design primer can amplify that gad gene. Methods: Isolation genomic form LAB, molecular identification based 16S rRNA, design primer use primer3plus, and use application serial cloner to ensure the primer can amplify to target gene. Results: That have been carried out based on the analysis of the 16 S rRNA gene have the highest similarity to Weissella confusa strain JCM 1093 with a similarity of 98.38%, while the results of the analysis of the gad gene with several primers that have been designed are not able to amplify the gad gene owned by W. confusa. Conclusion: The results of the analysis based on the 16S rRNA gene for lactic acid bacteria were obtained by Weissella confusa. However, for the results of identification analysis based on the gad gene, the designed primers were unable to amplify the gad gene in W. confusa.